PENGEMBANGAN E-MODUL BERBASIS PBL BERBANTUAN HEYZINE FLIPBOOKS SISWA KELAS VIII SMPN 14 MERANGIN - Prastia Wati; Muhammad Jainuri; Yohanes (Hira Institute, 2025)
The dearth of technology-based instructional materials that instructors employ to facilitate learning is the driving force for this study. The creation of reliable, useful, and efficient goods is the goal of this study. This type of research uses research and development (R&D) methods. PBL is the learning model that is employed. Analysis, design (planning), development, implementation, and evaluation are the five phases of the ADDIE development paradigm that are applied. The validation results for the very valid category showed that linguists received an average of 5.00, media experts received an average of 4.96, material experts received an average of 4.57, and practitioners received an average of 4.76. really legitimate category. The overall validation findings of the E-Module for Problem Based Learning (PBL) yielded a mean of 4.81 with a very valid category utilizing the Heyzine flipbook. In the practical area, 79.07% of the completed practicality questionnaire was collected. In the effective category, the percentage of student learning activities gained was 77.04, and the percentage of effectiveness of learning outcomes obtained was 84.61%. The E-Module based on Problem Based Learning (PBL) with the assistance of Heyzine flipbooks is valid, practical, and effective, and it may be employed in the mathematics learning process, according to the research and development findings